Advances in ubiquitous networking 2 : proceedings of the UNet'16 - El-Azouzi, Rachid; Menasche, Daniel Sadoc; Sabir, Essaid; Pellegrini, Francesco De; Benjillali, Mustapha (Springer, 2016)
This volume offers the proceedings of the 2nd UNet conference, held in Casablanca May 30 - June 1, 2016. It presents new trends and findings in hot topics related to ubiquitous computing/networking, covered in three tracks and three special sessions: Main Track 1: Context-Awareness and Autonomy Paradigms Track Main Track 2: Mobile Edge Networking and Virtualization Track Main Track 3: Enablers, Challenges and Applications Special Session 1: Smart Cities and Urban Informatics for Sustainable Development Special Session 2: Unmanned Aerial Vehicles From Theory to Applications Special Session 3: From Data to Knowledge: Big Data applications and solutions.
International conference proceedings.
Keywords: Ubiquitous computing -- Congresses.; Computer networks -- Congresses.; elektronické knihy; electronic books